KOMUNIKASI TRANSENDENTAL: SHALAT SEBAGAI BENTUK KOMUNIKASI TRANSENDENT - Robeet Thadi (JURNAL ILMIAH SYI'AR, 2017)
The term transcendental communication is a relatively new field of communication known in the area of   communication science studies. Therefore, many interpretations or definitions can be given to transcendental communication. Transcendental communication is vertical, and its form is not as concrete as the form and tradition of communication in general. If in interpersonal communication or group communication for example, the limits of each communication element (communicator, communicant, message, media, etc.) are very clearly visible, with relatively measurable results / effects. While in communication transendental elements of communication is not all can be detected in sensory. Therefore, within certain limits, it is not wrong to say that transcendental communication is private / abstract. To dissect the transcendental communication model, this paper would like to see prayer as a transcendental form of communication that is vertical between God to man or vice versa between man to the creator of Allah SWT.